On the taxonomy of the Exophyla-Isoura-Perinaenia generic-complex (Lepidoptera, Noctuidae, Catocalinae) - Babics, János; Ronkay, László (Zootaxa, 2011)
The genera Perinaenia and Isoura are revised, and four new species, P. mingchyrica sp. n. (Taiwan), P. atripunctum sp. n. (China, Shaanxi), P. nigrifascia sp. n. (Vietnam) and I. clara sp. n. (Nepal, Vietnam and Indonesia) are described. The systematic relationships of the genera Perinaenia, Isoura and Exophyla are discussed on the basis of their external and genitalic features.